1998
DOI: 10.1038/sj.gt.3300718
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses following direct injection of plasmid DNA into skeletal muscle

Abstract: Transfer of genes by injection of plasmid DNA into skeletal generated widespread inflammation of injected muscle, muscle has a wide variety of applications ranging from with mononuclear infiltrate, comprised largely of macrotreatment of neuromuscular disorders to genetic vacciphages and with both CD4 + and CD8 + T lymphocytes, nation. We examined each component involved in the present. Such inflammation may hamper clinical appliintramuscular injection of plasmid DNA in terms of the cation of this technology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 43 publications
2
61
1
Order By: Relevance
“…7,8 Nonviral delivery systems are safe and easy to apply, but suffer from low transduction efficiencies and can also cause local inflammatory reactions and tissue damage which may destroy transduced muscle fibres. 9 New methods have been examined for improving efficiency, using reagents such as cationic lipids and polymers. However, despite their success for gene transfer in vitro, results have been disappointing in muscle in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Nonviral delivery systems are safe and easy to apply, but suffer from low transduction efficiencies and can also cause local inflammatory reactions and tissue damage which may destroy transduced muscle fibres. 9 New methods have been examined for improving efficiency, using reagents such as cationic lipids and polymers. However, despite their success for gene transfer in vitro, results have been disappointing in muscle in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…12 Ultrasound is particularly effective for gene delivery when applied in combination with the use of microbubbles, cationic polymers or lipids. [3][4][5][6][7][8][9][10][11][12][13][14][15] Anwer et al 15 reported that application of ultrasound to skin tumours before or after the injection of lipoplexes resulted in a significant increase in gene transfer specifically to the tumour. 15 The magnitude of increased expression ranged from 3-4 to 270-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Naked plasmid DNA itself has low immunogenicity and can be administered repeatedly although local inflammatory reactions are still a concern. 19 The other major disadvantage reported is that plasmid DNA-mediated gene delivery with a foreign transgene driven by non-muscle specific promoters may evoke more severe immune responses to the transgene product than AAV vectors expressing the same protein. 20,21 The big drawback of plasmid DNA as a vector is its low efficiency for gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Gene Therapy (2001) 8, 1097-1107. duction in vivo. Although transduction yields are sufficient to trigger immune reactions in certain situations, [13][14][15][16] they would not reach the threshold required for the development of a functional benefit. The electrotransfer methodology has been recently adapted to skeletal muscle transduction in vivo with high efficacy and reproducibility, the expression of reporter or secreted proteins being increased by a factor of one to many hundreds.…”
Section: Introductionmentioning
confidence: 99%